Magnetic charged particles of optical spherical antiferromagnetic model with fractional system - Yao Shao-Wen (De Gruyter, 2021)
In this article, we first consider approach of optical spherical magnetic antiferromagnetic model for spherical magnetic flows of ϒΥ -magnetic particle with spherical de-Sitter frame in the de-Sitter space S12{{\mathbb{S}}}_{1}^{2}. Hence, we establish new relationship between magnetic total phases and spherical timelike flows in de-Sitter space S12{{\mathbb{S}}}_{1}^{2}. In other words, the applied geometric characterization for the optical magnetic spherical antiferromagnetic spin is performed. Moreover, this approach is very useful to analyze some geometrical and physical classifications belonging to ϒΥ -particle. Besides, solutions of fractional optical systems are recognized for submitted geometrical designs. Geometrical presentations for fractional solutions are obtained to interpret the model. These obtained results represent that operation is a compatible and significant application to restore optical solutions of some fractional systems. Components of models are described by physical assertions with solutions. Additionally, we get solutions of optical fractional flow equations with designs of our results in de-Sitter space S12{{\mathbb{S}}}_{1}^{2}.